Clamp cells for high pressure neutron scattering at low temperatures and high magnetic fields at Heinz Maier-Leibnitz Zentrum (MLZ). Issue 1 (2nd January 2021) - Eich, A.; Hölzle, M.; Su, Y.; Hutanu, V.; Georgii, R.; Beddrich, L.; Grzechnik, A.
ABSTRACT: We report on the feasibility of high pressure neutron scattering in clamp cells at various diffraction and spectroscopy beamlines in the Heinz Maier-Leibnitz Zentrum in Garching (Germany). The cells are compact in order to fit into the existing sample environment devices and to accommodate samples up to about 150 mm³ at pressures above 1 GPa.